HOLLAND’S THEORY: A COMPREHENSIVE OVERVIEW - Pleasant, Janeesha (Acta Scientiae et Intellectus, 2024)
This paper will discuss Holland’s Theory and the details that make up the RIASEC model. The author will discuss the typology that includes six personality types, six corresponding occupational environments, and their interactions that are offered as a tool for understanding work histories, vocational satisfaction, achievement, and vocational interest. The paper will also cover evidence based research that supports Holland’s theory. Readers will be able to understand the RIASEC model, and what assessments are based from the model.